From west to east; experience with adapting a curriculum in evidence-based medicine - Widyahening, I.S.; van der Heijden, G.J.M.G.; Moy, Foong Ming; van der Graaf, Y.; Sastroasmoro, S.; Bulgiba, Awang (2012)
Clinical epidemiology (CE) and evidence-based medicine (EBM) have become an important part of medical school curricula. This report describes the implementation and some preliminary outcomes of an integrated CE and EBM module in the Faculty of Medicine Universitas Indonesia (UI), Jakarta and in the University of Malaya (UM) in Kuala Lumpur. A CE and EBM module, originally developed at the University Medical Center Utrecht (UMCU), was adapted for implementation in Jakarta and Kuala Lumpur. Before the start of the module, UI and UM staff followed a training of teachers (TOT). Student competencies were assessed through pre and post multiple-choice knowledge tests, an oral and written structured evidence summary (evidence-based case report, EBCR) as well as a written exam. All students also filled in a module evaluation questionnaire. The TOT was well received by staff in Jakarta and Kuala Lumpur and after adaptation the CE and EBM modules were integrated in both medical schools. The pre-test results of UI and UM were significantly lower than those of UMCU students (p < 0.001). The post test results of UMCU students were comparable (p = 0.48) with UI, but significantly different (p < 0.001) from UM. Common problems for the modules in both UI and UM were limited access to literature and variability of the tutorsâ skills. Adoption and integration of an existing Western CE-EBM teaching module into Asian medical curricula is feasible while learning outcomes obtained are quite similar.